2015
DOI: 10.1111/eth.12380
|View full text |Cite
|
Sign up to set email alerts
|

Does Innovation Success Influence Social Interactions? An Experimental Test in House Sparrows

Abstract: In group‐living animals, individuals may benefit from the presence of an innovative group‐mate because new resources made available by innovators can be exploited, for example by scrounging or social learning. As a consequence, it may pay off to take the group‐mates' problem‐solving abilities into account in social interactions such as aggression or spatial association, for example because dominance over an innovative group‐mate can increase scrounging success, while spatial proximity may increase the chance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Furthermore, previous studies with these and other corvid species showed these birds to possess advanced cognitive abilities in both the social and physical domains (Emery & Clayton, 2004), and could therefore reasonably be expected to be able to make such an association. However, in house sparrows ( Passer domesticus ), model identity as an “innovator” following a demonstration of successful problem-solving performance to observers had no effect on their subsequent social interactions with the group ( Preiszner, Papp, Vincze, Bókony, & Liker, 2015). The authors suggested that observers may use other more subtle cues to determine the innovation abilities of their group-mates, rather than direct observation of their performance in an experimental setting (Preiszner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous studies with these and other corvid species showed these birds to possess advanced cognitive abilities in both the social and physical domains (Emery & Clayton, 2004), and could therefore reasonably be expected to be able to make such an association. However, in house sparrows ( Passer domesticus ), model identity as an “innovator” following a demonstration of successful problem-solving performance to observers had no effect on their subsequent social interactions with the group ( Preiszner, Papp, Vincze, Bókony, & Liker, 2015). The authors suggested that observers may use other more subtle cues to determine the innovation abilities of their group-mates, rather than direct observation of their performance in an experimental setting (Preiszner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, in house sparrows ( Passer domesticus ), model identity as an “innovator” following a demonstration of successful problem-solving performance to observers had no effect on their subsequent social interactions with the group ( Preiszner, Papp, Vincze, Bókony, & Liker, 2015). The authors suggested that observers may use other more subtle cues to determine the innovation abilities of their group-mates, rather than direct observation of their performance in an experimental setting (Preiszner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…poorer condition) among birds with similarly sized throat patches may be more motivated to compete for food, and hence may forage more aggressively and may win more encounters (e.g. Lendvai et al 2004, Preiszner et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation is that increased benefits of solvers may be negated by increased costs in urban habitats. For example, individuals with better problem-solving performance were found to be less competent in agonistic interactions Kozlovsky et al 2014Kozlovsky et al , 2015 or attacked more frequently by their flock mates , although the relationship between problem solving and competitiveness is not unequivocal (reviewed by Griffin and Guez 2014;Preiszner et al 2015;Quinn et al 2016). Thus, stronger competition for food during breeding in urban habitats (Foltz et al 2015) might reduce the reproductive payoffs of problem-solving skills.…”
Section: Discussionmentioning
confidence: 99%